Evaluación del volumen dispersado de los insecticidas caporal y cipermex, asperjados en plantas de cacao, y su efecto tóxico en el suelo, Moyobamba - Navarro Bardales,, Olivia (2014)
This research work was carried out from October 2012 to August 2013, he founded "Villa Floresta", Allmendra Sector, in the district and Moyobamba province, San Martin Department. The wording of the probtem was the following, is the volume dispersed from the insecticides "Caporal and Cipermex", sprayed in the cocoa plants, could cause toxicity in the soil? To demonstrate the hypothesis was: lf we disperse the insecticides "caporal and cipermex", sprayed in the cocoa plants, then cause toxicity in the soil. Taking as specific objectives, determine the volume of insecticides "Caporal and Cipermex'' that are located on the ground and in the cocoa plant, after the spraying; carry out the assessment of the toxicity of the insecticides "Caporal and Cipermex", located on the ground. In this experimental research design was used to complete random (DCA). The study area consisted of 3 sectors in evaluation, still 26 repetitions (13 plants for each insecticide) each sector presented 4 treatments consisting of high, medium, low, and soil. The evaluation of the volume dispersed from the insecticides "Caporal and Cipermex", was performed by direct impressions cardstock plasticized white 15 cm by 20 cm, the placement of the primers in the plants and the soil was in a systematic manner, depending on the cardinal points; two primers in each third · of the height of the plant and on the ground, in opposing positions, which were sprayed and visibly colored with aniline dissolved in water with insecticide. When determining the volume, we find that in the ground fell 0.0056 cc/cm2 of soil insecticida Cipermex, on average, of the three sectors and average of four applications, this amount is equivalent to 56 ce of solution 1m2 of soil, and as the mixture was 0.5 %, then fell 0.28 ce of venom/m2. And in the Caporal, was obtained 0.0058 ce of solution/cm2 on average of industries and applications, eqLJivalent to 58 ce of solution/m2 of soil. That is to say, on the ground fell 0.29 ce of venom/m2, because the mixture was 75 ce of venom in 15 liters of water. In sprays of Cipermex, the number of drops fallen was higher in the thirds medium, low, and soil. And spraying of the Caporal, the number of drops fallen was higher in the ground, in the middle and lower thirds. In the evaluations of the toxicity period of insecticidas "Chief' and "Cipermex" fallen in the soil, it was realized by means of the use of biomarkers. The contaminated soil was placed in tapers; then she was ranked 20 "termites" and after an hour with 30 minutes proceeded to tell individuals living and the dead. This procedure repeated itself for 1, 2, 3, 4 and 5 days in consecutiva form, after every aspersion. One did not find significant difference between insecticidas evaluated. According to the Analysis of Variance there was no significance in the number of "themes" live and number of "termites" dead on the floor with insecticidas residues Cipermex and caporal. In Duncan's test of the number of termites live and dead, was presentad statistical similarity, between the averages. In the test soil toxicity using chickens "bb", these birds showed no visible signs of toxicity, when you eat milled corn impregnated with 1 O grams of soil, extracted under plants treated with the insecticidas Cipermex and Caporal, from the first day of spraying. In conclusion, we demonstrated the hypothesis: lf we determine the volume of the insecticidas dispersad "caporal and cipermex", sprayed in the cocoa plants, then did not observe manifestations of toxicity in the biomarkers treaties with the ground, tested by the biomarkers chickens "bb", those who were not killed or presented visible symptoms of poisoning, ingesting ground corn impregnated with soil under cocoa plants, sprayed with insecticides evaluated. In the evaluations of the "termites" treated with soil extracted in the three sectors showed no significance in the analysis of variance, presented statistical similarity in Duncan test, in the evaluation of the live insects and in the evaluation of the dead insects. Key words: insecticides, toxicity period.